Evaluation of Anti-Diarrheal Activities of the 80% Methanol Extract and Solvent Fractions of Maesa lanceolata Forssk (Myrsinaceae) Leaves in Mice - Megersa A; Dereje B; Adugna M; Ayalew Getahun K; Birru EM (Dove Medical Press, 2023)
Alemayehu Megersa,1 Beyene Dereje,1 Meaza Adugna,2 Kefyalew Ayalew Getahun,2 Eshetie Melese Birru2 1Department of Pharmacology, School of Medicine, College of Medicine and Health Science, Dire Dawa University, Dire Dawa, Ethiopia; 2Department of Pharmacology, School of Pharmacy, College of Medicine and Health Science, University of Gondar, Gondar, EthiopiaCorrespondence: Alemayehu Megersa, Email aliemegersa@gmail.comBackground: Due to the limits of present antidiarrheal medications, it is critical to seek novel, safe, and inexpensive antidiarrheal agents. Thus, the goal of this study was to assess the antidiarrheal activity of 80% methanol crude extract and solvent fractions of Maesa lanceolata leaves in mice.Methods: Leaf powder was extracted by 80% methanol and then fractionated with n-hexane, ethyl acetate, and distilled water. At 100, 200, and 400 mg/kg, the effects of the crude extract on castor oil-induced diarrhea, enteropooling, and gastrointestinal motility tests were investigated. Tween 2% and atropine used as negative and positive controls, respectively. A gastrointestinal motility test was used to explore the anti-motility effects. Data were analyzed with SPSS V. 26, and the significance was established with a one-way ANOVA followed by a post hoc Tukey's test.Results: The crude extract delayed the onset of diarrhea and significantly reduced the number of fecal drops at 100 (p< 0.05), 200 and 400 mg/kg (p< 0.001). Similarly, the number and weight of wet feces, as well as total fresh feces, were reduced at 200 (p< 0.05) and 400 mg/kg (p< 0.001) compared to Tween 2%. The enteropooling test demonstrated that the extracts significantly reduced the volume and weight of intestine content at 200 (p< 0.05) and 400 mg/kg (p< 0.001). The anti-motility activity test revealed that the all extracts decreased gastrointestinal motility significantly (p< 0.001). The ethyl acetate fraction significantly reduced gastrointestinal transit time at all doses (p< 0.001). At 400 mg/kg, the activities of the n-hexane fraction were significant (p< 0.01). The efficacy of the residual aqueous fraction on gastrointestinal motility was significant at 200 (p< 0.05) and 400 mg/kg (p< 0.001).Conclusion: The 80% methanol extract of Maesa lanceolata Forssk leaf and solvent fractions were shown to exhibit potent antidiarrheal activity in the current study.Keywords: castor oil, crude extract, diarrhea, Maesa lanceolata Forssk, solvent fraction